Student Strategies for Improving The Quality of English Scientific Papers - Mikail Mega Maulana; Na’imah; Ilham Soleh Khudin (IKIP Siliwangi, 2024)
This study aims to explore student strategies for improving the quality of English-language scientific work. The approach used is a descriptive qualitative approach with primary data from in-depth interviews with 5 UIN Sunan Kalijaga Postgraduate students who have published English-language scientific papers in reputable journals, while secondary data are obtained from literature studies of literature relevant to the research topic. The results of this study show that the strategies used by students include 3 stages, namely: 1) Planning, which includes determining problem issues, research objectives, conceptual framework, research methodology, and research procedures. 2) Preparation of scientific papers, which includes selecting reputable journal portals, creating a frame of mind, managing finding and reference data, and correcting substances, grammar, and paragraph structure. 3) Translation, which includes strategies to improve the ability to translate scientific papers, the use of machine translation and grammar checkers, and finally feedback from English linguists to improve the quality of translation. This research provides important insights into students' efforts to improve the quality of English-language scientific work and its implications for the development of more effective teaching methods.